Acidity and Antioxidant Activity of Cold Brew Coffee - Rao, Niny Z. (Sci Rep, 2018)
The acidity and antioxidant activity of cold brew coffee were investigated using light roast coffees from Brazil, two regions of Ethiopia, Columbia, Myanmar, and Mexico. The concentrations of three caffeoylquinic acid (CQA) isomers were also determined. Cold brew coffee chemistry was compared to that of hot brew coffee prepared with the same grind-to-coffee ratio. The pH values of the cold and hot brew samples were found to be comparable, ranging from 4.85 to 5.13. The hot brew coffees were found to have higher concentrations of total titratable acids, as well as higher antioxidant activity, than that of their cold brew counterparts. It was also noted that both the concentration of total titratable acids and antioxidant activity correlated poorly with total CQA concentration in hot brew coffee. This work suggests that the hot brew method tends to extract more non-deprotonated acids than the cold brew method. These acids may be responsible for the higher antioxidant activities observed in the hot brew coffee samples.